Open management of surgical wounds subperitoneal rectum - Bermúdez Villegas, Jorge; Esperón, Alejandro; Veirano, Gustavo (Cirugía del Uruguay, 1991)
By means of a clinical study the possibility of leaving surgical wounds of subperitoneal rectum open, without the appearance of infection or healing disorders, in shown. This is supported with an experimental study in dogs. The reason why no infection occurs is not clear: a non-demonstrated hypothesis would be the protection created by anal dilation; in the case of dogs, /eaving the wound open is enough for protection. The possibility of a change of management of traumatic wounds of subperitoneal rectum is established.